Clinical and biochemical outcome of patients with polycystic ovary syndrome managed with life style modification or combination with metformin - Nabi, Md Masud Un; Pathan, Md Faruque; Barua, Milton; Kabir, Md Mahmudul; Alam, Md Jahangir; Jannut, Khandker Mahbuba (BIRDEM Medical Journal, 2019)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder with diverse reproductive and metabolic features. It is caused by insulin resistance that is exacerbated by obesity. Lifestyle modification is the first line treatment in PCOS, but it is associated with low adherence and sustainability. In small studies, metformin improves outcomes such as menstrual cycle problem, reduces the features of hyperandrogenism (hirsutism) and metabolic parameters (lipid profile). This study aimed to compare clinical and biochemical outcome of patients with polycystic ovary syndrome managed with life style modification or combination with metformin. Methods: This prospective interventional study was carried out at Endocrine OPD, BIRDEM, from November 2016 to March 2018. Newly detected cases of PCOS were taken as study sample. Sampling technique was purposive and then randomly selected into two groups; Group A (n=40) with lifestyle modification and Group B (n=40) with lifestyle modification plus metformin (500mg TDS). The clinical [weight, body mass index (BMI), waist circumference, menstrual problem, hirsutism) and biochemical [serum testosterone, LH, FSH, fasting lipid profile] outcome of intervention with lifestyle modification and combination with metformin was studied. Results: Baseline characteristics of both groups had no significant difference. After 12 months, there was significant improvement in hirsutism, menstrual problem and significant decrease in weight, BMI, waist circumference in both groups. Among hormonal profile there was significant reduction of testosterone in Group B (p=0.01), whereas LH, FSH and LH: FSH ratio showed no significant difference. There was significant improvement of HDL (in both groups) and reduction of triglyceride (TG) (p=0.005, in group B). Outcome differences between two groups had shown significant improvement in weight, BMI, testosterone, HDL, TG level and on menstrual regulation. But there was no significant difference in waist and Ferriman-Gallwayscore in between groups. Conclusion: lifestyle management is the first and most important step in the management of PCOS and addition of metformin to lifestyle modification appears to provide additional advantages. These results suggest the combination of lifestyle with metformin has a role to play in weight management: a key concern for women with PCOS. Addition of metformin also causes reduction of TG and testosterone, which is vital for PCOS management and found in this study. Birdem Med J 2020; 10(1): 26-33